2017
DOI: 10.3892/ijmm.2017.2961
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D attenuates hyperoxia-induced lung injury through downregulation of Toll-like receptor 4

Abstract: With considerable morbidity and mortality, bron-chopulmonary dysplasia (BPD) is a focus of attention in neonatology. Hyperoxia-induced lung injury has long been used as a model of BPD. Among all the signaling pathways involved, Toll-like receptor 4 (TLR4) has been demonstrated to play an important role, and is known to be regulated by vitamin D. This study aimed at elucidating the effect of vitamin D on hyperoxia-induced lung injury and the role of TLR4 in the process. Vitamin D was administered to hyperoxia-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
(37 reference statements)
2
25
0
Order By: Relevance
“…45 Other studies have proved that, in disease settings, vitamin D has positive effects on maintaining lung epithelial integrity and inhibiting inflammatory responses. 46,47 Vitamin D supplementation ameliorated pulmonary morphological alternations in LPS-induced bronchopulmonary dysplasia, inhibited IFN-γ overproduction and, thereby, suppressed inflammation. 48 Vitamin D was also confirmed to enhance the ability of neutrophils to kill Streptococcus pneumoniae and inhibit excessive inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…45 Other studies have proved that, in disease settings, vitamin D has positive effects on maintaining lung epithelial integrity and inhibiting inflammatory responses. 46,47 Vitamin D supplementation ameliorated pulmonary morphological alternations in LPS-induced bronchopulmonary dysplasia, inhibited IFN-γ overproduction and, thereby, suppressed inflammation. 48 Vitamin D was also confirmed to enhance the ability of neutrophils to kill Streptococcus pneumoniae and inhibit excessive inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…VD also plays a crucial role in cellular growth and differentiation, including the regulation of lung maturation ( 15 ). Moreover, the impact of VD on early lung development and BPD has become an emerging field of research in recent years ( 18 , 20 ). Yao et al ( 20 ) suggested that VD attenuated hyperoxia-induced lung injury by protecting the integrity of the lung structure, decreasing extracellular matrix deposition, inhibiting inflammation, and antagonizing the activation of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…A low VD level at 24 h of life was shown to be a risk factor for the development of BPD ( 17 ), and a lower VD level was associated with the increased severity of BPD ( 18 ). Studies have demonstrated that VD could attenuate lung injury in an animal model of BPD through the suppression of interferon-gamma (IFN-γ) production ( 19 ) or downregulation of Toll-like receptor 4 (TLR4) ( 20 ); however, the mechanism of VD in BPD remains poorly understood and uncertain. Because VD can decrease NETs activity ( 21 ), we hypothesized that VD plays a protective role against BPD by regulating NETs.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were aimed at Toll-interleukin 1 receptor domain-containing adaptor protein (TIRAP). Researchers have also found that TLR5 and TLR4 were associated with the occurrence of BPD via the MyD88-dependent pathway [33,34], and TLR10 was reported to active the TRL4 signaling pathway. So, TLR10 might also be related to the occurrence of BPD; another nding that requires con rmation.…”
Section: Discussionmentioning
confidence: 99%